Application of the Jarimatics Method in Mathematics Learning to Increase the Ability of Students of Class V Min 2 Palangka Raya in Calculate Multiplication - Mutiarani Pionera; Supriadi Supriadi; Kumalasari Kumalasari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Calculating multiplication in Mathematics for the 5th-grade students of MIN 2 Palangka Raya only relied on the teacher's direct instruction through a series of formulas which made students feel bored, unactivated, and burdened (especially for those who are weak in memorizing the formulas). This study aims to improve the ability to calculate the multiplication of the students through the implementation of Jarimatika. This research is a Classroom Action Research (CAR) consisting of two cycles. The data of the students' abilities in calculating multiplication obtained in the first cycle reached 64 or around 40.5% while it in the second cycle reached 76 or around 81%. The results showed that students' learning activities through Jarimatika method became more active. In addition, their ability to calculate multiplication was also successfully increased.